Predictors of 30-Day Readmission for Pneumonia. (February 2016) - Flanagan, Jane; Stamp, Kelly D.; Gregas, Matt; Shindul-Rothschild, Judy
Abstract : OBJECTIVE: This study examined data from 4 sources: number of hospital-acquired conditions, patient perception of care, quality outcome measures, and demographic data to explain variances associated with 30-day pneumonia readmission rates. BACKGROUND: Patients readmitted within 30 days for pneumonia increases the length of hospital stay by 7 to 9 days, increases crude mortality rate 30% to 70%, and costs of 40 000 or greater per patient. METHODS: Variances in outcomes measures associated with 30-day pneumonia readmissions from 577 nonfederal general hospitals in Massachusetts, California, and New York were analyzed using datasets from Hospital Consumer Assessment of Healthcare Providers and Systems, Centers of Medicare & Medicaid Services, Agency for Healthcare Research and Quality, and American Hospital Association. RESULTS: Three factors increased pneumonia readmission rates: poor nurse-patient communication, poor staff responsiveness to patient needs, and iatrogenic pneumothorax. Conversely, factors lowering pneumonia readmission rates included patients hospitalized in California, higher RN staffing, and higher proportions of nursing staff to total hospital personnel. CONCLUSION: Findings suggest lower nurse staffing, poor nurse-patient communication, and nurse responsiveness to patient needs contribute to increased pneumonia readmission rates.